The Internet and social inequalities - Witte, James C.; Mannon, Susan E. (Contemporary sociological perspectives, 2010)
Suitable for use as a core or secondary text in lower division social inequalities or social problems courses, this book explains how the changing nature and uses of the Internet not only mirror today's social inequalities, but also are at the heart of how stratification is now taking place.